2021
DOI: 10.1097/01.ogx.0000791684.08887.ef
|View full text |Cite
|
Sign up to set email alerts
|

Position and Integrity of Uterine Scar Are Determined by Degree of Cervical Dilatation at Time of Cesarean Section

Abstract: Analyses of treatment covariate interactions found no clear evidence that the relative effects of vaginal progesterone or 17-OPHC differed based on cervix length, or by history of a prior preterm birth. However, because the underlying risk of preterm birth is greater at shorter cervical lengths, the absolute risk reductions were greater for women with a shorter cervix. There was no apparent benefit of treatment in the women with a prior preterm birth and cervical length greater than 30 mm.So, what are the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…A recent cohort study has found that elective and early labour CD at cervix dilatation < 2cm is associated with an increased prevalence of a scar above the internal cervical os as well as a scar niche. 31 In the present study, we found a significantly (P<0.001) higher incidence of a uterine niche in women who had an elective compared to those who had an emergent CD. When the CD was performed at a cervical dilatation < 4 cm there was a significantly (P=0.027) higher incidence of a uterine niche located above the vesicovaginal fold and a significantly (P=0.0002) lower proportion of cesarean scar below the vesicovaginal fold compared to those who had their CD at active stage of labour.…”
Section: Discussionsupporting
confidence: 49%
“…A recent cohort study has found that elective and early labour CD at cervix dilatation < 2cm is associated with an increased prevalence of a scar above the internal cervical os as well as a scar niche. 31 In the present study, we found a significantly (P<0.001) higher incidence of a uterine niche in women who had an elective compared to those who had an emergent CD. When the CD was performed at a cervical dilatation < 4 cm there was a significantly (P=0.027) higher incidence of a uterine niche located above the vesicovaginal fold and a significantly (P=0.0002) lower proportion of cesarean scar below the vesicovaginal fold compared to those who had their CD at active stage of labour.…”
Section: Discussionsupporting
confidence: 49%
“…In addition, taking large doses of oxytocin can also cause side effects such as hypotension and arrhythmia. Our study showed that carbetocin has a good hemostatic effect, and the effect is rapid and long-lasting [8][9][10]. is method has been well applied in the cesarean section of pregnancy with a uterine scar.…”
Section: Discussionmentioning
confidence: 99%
“…Remodeling of the lower uterine segment after Cesarean delivery (CD) can lead to Cesarean scar defect, which can range from a small defect of the superficial myometrium to a deep defect or niche 4 . The incidence of Cesarean scar defect increases with the number of prior CDs and is influenced by the hysterotomy closure technique used and scar location [4][5][6] . After multiple lower-segment CDs, the anterior uterine wall becomes thinner and largely consists of fibrotic scar tissue [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%